2021
DOI: 10.1002/asjc.2581
|View full text |Cite
|
Sign up to set email alerts
|

Variance‐constrained resilient H filtering for mobile robot localization under dynamic event‐triggered communication mechanism

Abstract: This paper is concerned with the mobile robot localization problem subject to filter gain uncertainty under dynamic event-triggered communication mechanism, and meanwhile, the H ∞ filtering performance and the error variance constraint are guaranteed. For saving the sensor energy, a dynamic event-triggered communication mechanism is introduced to manage the transmission of the measurement data from the sensor to the filter. To characterize the possible fluctuations of the desired filter gain, a resilient filte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Lemma [27]. Given constant matrices W1,0.1emW2$$ {W}_1,{W}_2 $$, and W3$$ {W}_3 $$ , where W1=W1T$$ {W}_1&amp;#x0003D;{W}_1&amp;#x0005E;T $$, and 0<W2=W2T$$ 0&amp;lt;{W}_2&amp;#x0003D;{W}_2&amp;#x0005E;T $$, the inequality W1+W3TW21W3<0$$ {W}_1&amp;#x0002B;{W}_3&amp;#x0005E;T{W}_2&amp;#x0005E;{-1}{W}_3&amp;lt;0 $$ is equivalent to []center centerarrayW1arrayW3TarrayW3arrayW2<0.5emor.5em[]center centerarrayW2arrayW3arrayW3TarrayW1<0.$$ \left[\begin{array}{cc}{W}_1&amp;amp; {W}_3&amp;#x0005E;T\\ {}{W}_3&amp;amp; -{W}_2\end{array}\right]&amp;lt;0\kern.5em \mathrm{or}\kern.5em \left[\begin{array}{cc}-{W}_2&amp;amp; {W}_3\\ {}{W}_3&amp;#x0005E;T&amp;amp; {W}_1\end{array}\right]&amp;lt;0.…”
Section: Resultsmentioning
confidence: 99%
“…Lemma [27]. Given constant matrices W1,0.1emW2$$ {W}_1,{W}_2 $$, and W3$$ {W}_3 $$ , where W1=W1T$$ {W}_1&amp;#x0003D;{W}_1&amp;#x0005E;T $$, and 0<W2=W2T$$ 0&amp;lt;{W}_2&amp;#x0003D;{W}_2&amp;#x0005E;T $$, the inequality W1+W3TW21W3<0$$ {W}_1&amp;#x0002B;{W}_3&amp;#x0005E;T{W}_2&amp;#x0005E;{-1}{W}_3&amp;lt;0 $$ is equivalent to []center centerarrayW1arrayW3TarrayW3arrayW2<0.5emor.5em[]center centerarrayW2arrayW3arrayW3TarrayW1<0.$$ \left[\begin{array}{cc}{W}_1&amp;amp; {W}_3&amp;#x0005E;T\\ {}{W}_3&amp;amp; -{W}_2\end{array}\right]&amp;lt;0\kern.5em \mathrm{or}\kern.5em \left[\begin{array}{cc}-{W}_2&amp;amp; {W}_3\\ {}{W}_3&amp;#x0005E;T&amp;amp; {W}_1\end{array}\right]&amp;lt;0.…”
Section: Resultsmentioning
confidence: 99%
“…Denoting the one-step prediction error as e k+1|k = X k+1 − Xk+1|k and combining (10) and (12), one has…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, the mobile robot (MR) has played a vital role in many application areas such as unmanned vehicle navigation, intelligent manufactory, and aerospace [1][2][3]. As a significant issue in the MR research field, the MR localization (MRL) problem (MRLP) has aroused particular research interests, and a great quantity of attention-getting results have been reported in the existing literature, see, for example, other studies [4][5][6][7][8][9][10][11][12]. For instance, in Yang et al [13], the MRLP has been solved by developing a robust extended H ∞ filtering method.…”
Section: Introductionmentioning
confidence: 99%
“…In the existing literature, one of the commonly used schemes is to introduce model uncertainties accounting for inaccurate measurement-induced unknown bias, see, for example [12,13]. For the sake of decreasing the effect of model uncertainties on the system performance, a number of approaches have been developed and, accordingly, some representative research results have been published for linear systems [14], nonlinear systems [15], master-slave systems [16], neutral systems [17], robotic manipulators [18], unmanned aerial vehicles [19] and marine vehicles [20].…”
Section: Introductionmentioning
confidence: 99%